2013
DOI: 10.1002/jobm.201300433
|View full text |Cite
|
Sign up to set email alerts
|

Serine protease identification (in vitro) and molecular structure predictions (in silico) from a phytopathogenic fungus,Alternaria solani

Abstract: Serine proteases are involved in an enormous number of biological processes. The present study aims at characterizing three‐dimensional (3D) molecular architecture of serine proteases from early blight pathogen, Alternaria solani that are hypothesized to be markers of phytopathogenicity. A serine protease was purified to homogeneity and MALDI‐TOF‐MS/MS analysis revealed that protease produced by A. solani belongs to alkaline serine proteases (AsP). AsP is made up of 403 amino acid residues with molecular weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…We also noticed the dielectric constant and conductivity behavior of A. solani are higher than any other foliar causing fungal pathogen tested. Although some studies have reported that cytoplasmic components of A. solani are hydrophobic, others have indicated polar and hydrophilic amino acids in its cytoplasm [43], [44]. In fact, the cationic and hydrophobic features are associated with microbial peptides interacting primarily with negatively charged biomembranes [45], [46]; such membrane effect is pronounced at low frequency.…”
Section: Resultsmentioning
confidence: 99%
“…We also noticed the dielectric constant and conductivity behavior of A. solani are higher than any other foliar causing fungal pathogen tested. Although some studies have reported that cytoplasmic components of A. solani are hydrophobic, others have indicated polar and hydrophilic amino acids in its cytoplasm [43], [44]. In fact, the cationic and hydrophobic features are associated with microbial peptides interacting primarily with negatively charged biomembranes [45], [46]; such membrane effect is pronounced at low frequency.…”
Section: Resultsmentioning
confidence: 99%
“…Extracellular proteases are key enzymes produced by fungi during the host-pathogen interaction and are involved in growth, development, survival and pathogenicity [ 31 ]. The presence of an extracellular serine protease and metalloprotease was recently found to be secreted by A. solani and proposed to be involved in phytopathogenicity [ 32 , 33 ]. However, additional molecular studies are needed to demonstrate that they play a role in virulence.…”
Section: Early Blightmentioning
confidence: 99%
“…The fungal deuterolysin metalloprotease (M35) family was reported to be involved in cell wall degradation, epidermal growth inhibition, and cell activity of insects ( Huang et al, 2020 ). The serine protease is an important pathogenic marker for Alternaria solani ( Chandrasekaran et al, 2014 ). We presumed that these deduced secreted proteins in pathogen of tobacco target spot may serve as potential effectors that may play important roles in the pathogenicity of fungus, and remains to be further investigated in the following work.…”
Section: Discussionmentioning
confidence: 99%